KAJIAN KITAB DIRẬSẬT FĪ AL-HADĪTH WA AL-TARĪKH: AHẬDĪTH UMMUL MUʻMINĪN ‘ẬISYAH KARYA MURTAḌA AL-‘ASKARĪ - Kholila Mukaromah (LPPM IAIN Kediri, 2019)
‘Aisyah wa one of the wives of the Prophet Pbuh. who atrracted much attention. Among the Sunni, he received much praises –for one thing- because of the breadth and depth of his knowledge, as well as the narration and mastery of his hadith which were considered to be prominent among of the other wives of the Prophet Pbuh. On the contrary, there was a group of people from Shia who instead denounced and cursed ‘Aisha. Starting from this, the author was interested to explore one of the hadith books that tells how the figure of ‘Aisha based on the narration of hadiths compiled by a Shia scholar , Murtada al-‘Askari. The writing of al-‘Askari can be counterweight to the “bad image” that has been given by the Shia to ‘Aisha. One interesting view was also conveyed by al-‘Askari is that the history of Islam ( from sending of the Prophet Pbuh. to the pledge of Yazid bin Mu’awiyah) can only be truly understood after examining the hadith narration of ummul mu’mini>n, ‘Aisha. This research is a literatur review. The discussion of which uses descriptive-analytical method. This paper generally tries to introduce the hadith book titled Dira>sa>t fi> al-Hadi>th wa al-Tari>kh : Aha>dith Ummul Mu’mini>n ‘Aisha by looking at some general aspects of the composition of the book, including writing background, content, systematic, method, examples of discussion, and also describes the advantages and disadvantages analyzed from several section of the book. Based on the results of the discussion, the author considers that al-‘Askari tried to put a description of the figure ‘Aisha objectively based on the historical hadiths that originated from ‘Aisha and also the the other companins (sahabah) about ‘Aisha and the event surrounding herself. In discussing the death of the Prophet Pbuh., al-‘Askari included a variety of narration that seems contradictory about the Prophet’s death moments,”whether in the lap of ‘Aisha or ‘Ali?!”. Based on the tarji>h method, al-‘Askari more favored the narration of hadith which said that the Prophet Pbuh had died in the lap of ‘Ali because more were narrated ( four companions /sahabah). Interestingly, the source of the narration referred to by al-‘Askari is almost entirely derived from a number of well-known Sunni scholars. This was done to show how scientific research must be carried out without looking at affiliations of certain religious sects.",